Jasmonates disrupt carrageenan synthesis during carposporogenesis in the red seaweed Grateloupia imbricata - Del Rosario-Santana, Diana; Robaina, Rafael; Garcia-Jimenez, Pilar (Frontiers in Marine Science, 2023)
In this study, we monitored changes in cell wall sulfated galactans in the red seaweed Grateloupia imbricata after the rapid (48 h) induction of cystocarp maturation and carpospore development by the volatile hormone methyl jasmonate (MEJA). Synthesis of sulfated galactans, carrageenans, which requires sulfated UDP galactose, was followed by expression analysis of genes encoding phosphoglucomutase (PGM), galactose-1-phosphate uridyltransferase (GALT), and those responsible for sulfate assimilation (S-transporter and sulfate adenylyltransferase, SAT). In addition, the expression of carbohydrate sulfotransferase and galactose-6-sulfurylase responsible for the addition and removal of sulfate groups to the galactans backbone were evaluated. Structural changes, such as thallus softening, were analyzed using Fourier-transformed infrared spectroscopy (FTIR) spectra, and ploidy was assessed using flow cytometry. The results showed downregulation of most of the genes encoding precursors or those in charge of transformation into sulfated hexoses for cell wall synthesis. Furthermore, alterations in the FTIR spectrum of carrageenan from MEJA-induced fertile thalli, such as the disappearance and flattening of absorption bands, were observed. The promptness of these events and the ploidy of thalli and spores seem to confirm the induction of mitotic production of haploid spores by MEJA.